Hubungan Antara Kompensasi Dan Pengembangan SDM Dengan Kepuasan Kerja Karyawan (Studi Kasus PT. Sinar Murni Indoprinting) - Cindy Choridatul Muawanah; Aizzatul Laila; Ayu Lucy Larassaty (BADAN PENERBIT STIEPARI PRESS, 2023)
Compensation is one of the driving factors (motives) in the process of occurrence of an activity in a job. Compensation in a job can also or can be used as a benchmark or determinant of whether or not the company's ability to appreciate the workers in their work is good and apart from that the effect of giving good compensation will make employees active and active in their work. Apart from that, the size of the amount of compensation given, including a sense of fairness in the awarding process, compensation can cause other things such as job satisfaction of employees. The purpose of this description is to see the relationship between compensation, HR development and employee job satisfaction. The discussion uses data from PT. Sinar Murni Indoprinting using a sample of 100 people. From the results of calculations using the SPSS version 25 application, it was found that there was a good relationship, namely at 52,7 percent. This shows that there is a strong relationship between compensation variables and job satisfaction variables.